How subsidiarity and international consensus shape the way the European Court of Human Rights uses scientific data (TEST BioLaw Journal - Rivista di BioDiritto, 2024)
This paper explores the relationship between the European Court of Human Rights and the use of scientific data. It is argued that, just as any other judicial proceedings, scientific data may be relevant to the decision of the Court as they may shed light on the factual background of the case. However, the special features of the ECHR mechanism require the Court to look at scientific data mainly through the lens of the principle of subsidiarity and consensus within contracting States.
Keywords: European Court of Human Rights; ECHR; scientific data; subsidiarity; consensus